Synthesis of hybrid metal–organic frameworks of FexMyM′1−x−y-MIL-88B and the use of anions to control their structural features. Issue 37 (12th September 2016) - Choi, Sora; Cha, Wonhee; Ji, Hoyeon; Kim, Dooyoung; Lee, Hee Jung; Oh, Moonhyun
Abstract : The structural features of micro-sized metal–organic framework particles are rationally controlled by altering the anions involved in the structure. Abstract : The controlled formation of metal–organic frameworks (MOFs) or coordination polymers (CPs) with suitable components and structural features is one of the most important themes in MOF research. In particular, the reliable preparation of hybrid MOFs containing more than two different kinds of metal ions or organic linkers and a comprehensive understanding of the structural flexibility of MOFs are the central issues for the production of MOFs with the desired properties. We report the synthesis of micro-sized hybrid MOF particles [also known as coordination polymer particles (CPPs)] containing two or three kinds of metal ions in each particle: Fe x M y M′1− x − y -MIL-88B (MIL stands for Materials of Institut Lavoisier, M and M′ = Ga, Co, or Mn). Scanning electron microscopy images revealed the formation of well-defined uniform micro-sized hexagonal rods, and energy-dispersive X-ray spectroscopy and elemental mapping images verified the simultaneous incorporation of two or three kinds of metal ions within the CPPs. Interestingly, the structural features of CPPs made from MIL-88B were controlled by altering the anions involved in the structure. Incorporating large acetylacetonate anions within the structure resulted in the closed MIL-88B structure with a small cell volume. However, the open MIL-88B structure with a large cell volume was obtained when small chloride anions were incorporated. The intermediate semi-open MIL-88B structure was also prepared using nitrate anions. Three different structural forms of MIL-88B were verified by powder X-ray diffraction, whole pattern fitting, and thermogravimetric analysis.